Analysis of Students’ Physics Critical Thinking Ability in Problem-Based Learning Models Assisted With Video - Oktiana, Rohmiati; 'Ardhuha, Jannatin; Makhrus, Muh. (Empiricism Journal, 2023)
Critical thinking skills are one of the abilities that students must have in order to facilitate processing and analyzing the information obtained, as well as selecting or making the right decision about a problem in physics learning. This study aims to measure students' critical thinking skills using a video-assisted problem-based learning model. Syllabus, lesson plans, teaching materials, worksheet, learning videos, and test instruments are learning tools on elasticity and Hooke's law that support this research. The research method uses a quasi experiment with a One-Group-Pretest-Posttest design. A total of 30 students in class XI MS 2 in the odd semester of the 2022/2023 school year at SMAN 1 Kediri became research participants. Data collection techniques using worksheet and critical thinking ability test instruments. worksheet is used in order to facilitate critical thinking skills during learning activities, and the assessment scores are converted into percentages and then classified into the criteria for critical thinking skills. Test instruments are also used as pretests and posttests to measure critical thinking skills before and after learning activities, and the results are analyzed using the N-Gain test and interpreted into effectiveness interpretations. The results of the worksheet assessment showed that students' critical thinking skills were 82.22% with very critical criteria, and the N-Gain test instrument was 0.57 in the moderate improvement category and included in the criteria for being quite effective. So it can be concluded that there is an increase in students' critical thinking skills by using a video-assisted problem-based learning model and effective use in learning.